2017
DOI: 10.1016/j.jcin.2017.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Abnormalities and Permanent Pacemaker Implantation After Transcatheter Aortic Valve Replacement Using the Repositionable LOTUS Device

Abstract: Following implantation of the repositionable LOTUS valve, 55% of patients developed LBBB and 32% of patients required a pacemaker during their index hospital admission. Patients with pre-procedural conduction disturbance and non-calcified aortic valves were more likely to need pacing. No other anatomic features were identified with increased pacing requirement with the LOTUS device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Post- balloon dilatation failed to show significant impact on pacing following TAVR in an isolated Lotus valve cohort with 228 patients, and a remarkable PPI rate of 32% with a median time to PPI of 3.0 days. [ 20 ][ 21 ][ 22 ]. It was presumed that pre-dilatation may avoid the need for post-dilatation(17).…”
Section: Discussionmentioning
confidence: 99%
“…Post- balloon dilatation failed to show significant impact on pacing following TAVR in an isolated Lotus valve cohort with 228 patients, and a remarkable PPI rate of 32% with a median time to PPI of 3.0 days. [ 20 ][ 21 ][ 22 ]. It was presumed that pre-dilatation may avoid the need for post-dilatation(17).…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by these findings, considerable effort has been invested to elucidate the underlying mechanisms of this elevated PPI rate of the Lotus valve system. In a study by Rampat et al, excluding patients with a pacemaker at baseline, new PPI rate was 32% and was only predicted by baseline conduction abnormalities (11). In a recent subanalysis of the REPRISE IIE trial, implantation technique (implantation depth >5 mm) and annular oversizing (defined as LVOT overstretch of >10%) were identified as predictors for new PPI (6).…”
Section: Editorialmentioning
confidence: 99%
“…Notably, an implantation depth of ≤6 mm was associated with a lower incidence of PPI compared with deeper implants with CoreValve (29); however, the UK experience with the Lotus Valve TM showed a mean implantation depth of 5.7±3.2 mm in the overall cohort. Hence, implantation depth was not found a predictor of PPI (24). Based on its mechanically expansion, the radial force of this device may be greater than the CoreValve TM .…”
Section: Need For Permanent Pacemaker Implantation (Ppi)mentioning
confidence: 78%
“…This result is not surprising since studies with Lotus Valve TM have consistently reported high (30-36%) rates of PPI ( Table 1). In the United Kingdom Experience (24), the incidence of new left bundle brunch block was 55% and 32% of the patients required PPI after Lotus Valve TM implantation (24). These rates are higher than those reported in studies with the selfexpanding Accurate TA (8) and Acurate Neo (9) devices (Symetis, S.A., Ecublens, Switzerland/Boston Scientific, Marlborough, MA, USA) that is 5-10% and CoreValve (Medtronic, Inc., Minneapolis, Minnesota, USA), that is 15-26% (2,4,(25)(26)(27).…”
Section: Need For Permanent Pacemaker Implantation (Ppi)mentioning
confidence: 99%